PENGARUH POLA ASUH “GRAND PARENTING” TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA SEKOLAH DASAR - Muhammad Nasrul Waton (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2022)
Abstract: The number of mother figures in the family who enter the world of work outside the home and leave their families turns out to have quite significant consequences, especially related to child care. In the culture of our society in the past, the task of parenting was dominated by the mother. In the current era of industry 4.0, many mothers have started to work and even become a pillar of socio-economic life which is no less important than their husbands, the task of childcare begins to shift. Changes in the mother's role have an impact on substitute care for other family members. A child is a representative of both parents, he is a living being that will continue to grow and develop every time. Cognitive development of elementary school age children cannot be equated with adolescents or adults, the cognitive development of elementary school age children is very limited for concrete (real) matters. Based on the background and problem identification, the research problem is formulated as follows: How much influence does grand parenting have on cognitive development in students whose mothers are factory employees at SD Negeri 193 Gresik? There is no significant effect between grand parenting and cognitive development of students in grade IV from 2 classes at SD Negeri 193 Gresik. This is evidenced by the results of the product moment correlation analysis of 0.089 compared to the t-table level of significance 5% N=40 of 2.042. So the t-count is smaller than the t-table, it can be interpreted that the null hypothesis (Ho) that is there is no effect of grand parenting on the cognitive development of students in grade IV of 2 classes at SD Negeri 193 Gresik is accepted. And the hypothesis (Ha) that there is an effect of grand parenting on students' cognitive development in grade IV students from 2 classes at SD Negeri 193 Gresik is rejected. Based on the description above, it can be concluded that grandmother's care does not have a significant effect on students' cognitive development.